Micro-Livestock and Macro-Impact with A Goat Farming Empowerment Program - Rahman, Sarli; Dalil, M; Jahrizal, Jahrizal; Junaedi, Achmad Tavip; Renaldo, Nicholas; Marlim, Yulvia Nora; Susanti, Wilda; Koto, Jaswar; Musa, Sulaiman; Wahid, Nabila; Cecilia, Cecilia (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
This program is designed to provide hands-on training, resources, and long-term support to individuals and families, especially women and youth, in rural areas. By equipping participants with the knowledge and tools necessary for successful goat rearing, the program not only creates opportunities for additional income but also strengthens food resilience and self-sufficiency at the grassroots level. This community service program employs a participatory and sustainable development approach to implement goat farming as a tool for empowerment and livelihood improvement. The methodology consists of five main phases: community assessment, participant selection, training and capacity-building, implementation, and monitoring & evaluation. The Micro-Livestock and Macro-Impact program demonstrated that small-scale goat farming can serve as a powerful tool for community empowerment, particularly in rural areas with limited income sources. Through training, resource provision, and cooperative support, participants significantly improved their knowledge, increased their household income, and began to experience the benefits of sustainable livestock management. The success of this program highlights the potential of micro-livestock farming to serve as a replicable and scalable model for rural development. It shows that even small agricultural interventions, when paired with training and community engagement, can lead to measurable improvements in food security, income generation, and social empowerment.